HUBUNGAN PENGETAHUN IBU DENGAN PEMBERIAN MP-ASI PADA ANAK USIA 6-24 BULAN DI WILAYAH KERJA PUSKESMAS BUMIWONOREJO KABUPATEN NABIRE PROVINSI PAPUA - NUR AL-FAIDA (J-KESMAS: Jurnal Kesehatan Masyarakat, 2023)
ABSTRACTThe purpose of this study was to see whether there was a relationship between mother's knowledge and the provision of complementary feeding to children aged 6-24 months in the working area of the Bumiwonorejo Public Health Center, Nabire Regency, Papua Province. This research is a quantitative research, with a cross sectional research design. This research was conducted from May to July 2022 in the Working Area of the Bumiwonorejo Health Center. The population in this study were all mothers with children aged 6-24 months who came to the posyandu in the working area of the Bumiwonorejo Health Center as many as 40 people. The research sample was 40 respondents with a sampling technique using a total sampling technique. The research instrument used was a list of questions in the form of a questionnaire. The data obtained were processed using SPPS and analyzed using the chi-square test. The results of this study indicate that there is a significant relationship between mother's knowledge and the provision of complementary feeding to children aged 6-24 months, the p value (value) = 0.02. Based on the results of the research obtained, the researchers suggest to mothers, especially those with babies aged 0 to 6 months, to pay more attention to the provision of complementary foods that are too fast.